2021
DOI: 10.3390/ijerph18041403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Urbanization on Carbon Emissions in Urban Agglomerations of the Middle Reaches of the Yangtze River

Abstract: The urban agglomerations in the middle reaches of the Yangtze River (MYR-UA) are facing a severe challenge in reducing carbon emissions while maintaining stable economic growth and prioritizing ecological protection. The energy consumption related to land urbanization makes an important contribution to the increase in carbon emissions. In this study, an IPAT/Kaya identity model is used to understand how land urbanization affected carbon emissions in Wuhan, Changsha, and Nanchang, the three major cities in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 61 publications
0
25
1
Order By: Relevance
“…The rationalization of industrial structure refers to the aggregation quality between industries, reflects the coordination degree and sufficient utilization degree of resources between industries, and measures the coupling degree of factor input structure and output structure. This paper refers to the research results of Gan (2011) and Zhang (2018), who used the Theil index to calculate the industry rationalization index [30,31]. Theil index represents regional economic disparity, and the value is proportional to the degree of distinction.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The rationalization of industrial structure refers to the aggregation quality between industries, reflects the coordination degree and sufficient utilization degree of resources between industries, and measures the coupling degree of factor input structure and output structure. This paper refers to the research results of Gan (2011) and Zhang (2018), who used the Theil index to calculate the industry rationalization index [30,31]. Theil index represents regional economic disparity, and the value is proportional to the degree of distinction.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…For instance, Zhou et al (2019) suggested a Kuznets curve relationship between economic urbanization and carbon emissions, and they also claimed that energy consumption related to land urbanization greatly contributes to the increase in carbon emissions. Besides, urban expansion is more significant than economic growth in promoting carbon emissions (Zhang et al, 2021). Population and gross regional domestic product (GRDP) are positively correlated with carbon emissions, and the entire built-up and urban road areas are positively correlated with carbon emissions (Pu et al, 2020;Zhang et al, 2022).…”
Section: Literature Review and Hypotheses Previous Research On Urbani...mentioning
confidence: 99%
“…The leading and emerging industries with high‐tech as the core will further improve resource utilization efficiency, thus changing the overall structure of social resource use. An improved resource utilization rate and an emerging environmental pollution control technology will further reduce the environmental impact and thus improve ecological efficiency (Zhang and Cui 2018). The rationalization of industrial structure refers to the process of pursuing moderate industrial scale and a balanced growth rate.…”
Section: Theoretical Analysis Frameworkmentioning
confidence: 99%